Role of International Higher Education in Developing Employability: Limitations and Opportunities - Masum, Fahria (Richtmann Publishing, 2012)
Employability of graduates is one of the current policy concerns emerging in higher education developments and theimplementation of Bologna process. It calls for a continued proactive role of universities and other higher education institutionstoward developing lasting employability. The research was conducted to evaluate the performance of the MSc Programme LandManagement and Land Tenure at Technische Universitaet Muenchen, Germany in developing better employability of theirstudents. 39 alumni took part in questionnaire survey and focus group discussion. The survey results showed high levels ofgraduates’ satisfaction concerning studies in MSc Programme Land Management and Land Tenure as a whole. During interviewthe alumni also confirmed that different aspects of the academic programme (e.g. curriculum, international experience, alumninetworks) had the highest influence on their career development. However, some factors were identified which hinder theemployability opportunity of alumni.